Diversity of the Swine Leukocyte Antigen Class I and II in Commercial Pig Populations - Techakriengkrai, Navapon; Nedumpun, Teerawut; Golde, William T.; Suradhat, Sanipa (Frontiers in Veterinary Science, 2021)
Among swine genetic markers, the highly polymorphic swine leukocyte antigen (SLA) is one of the key determinants, associated with not only immune responses but also reproductive performance and meat quality. The objective of this study was to characterize the SLA class I and II diversities in the commercial pig populations. In this study, a total number of 158 pigs (126 gilts and 32 boars) were randomly selected from different breeding herds of 5 major pig-producing companies, which covered approximately 75% of Thai swine production. The results indicate that SLA class I and II were highly diverse in the Thai population. The highly common SLA class I alleles were SLA-1*08XX, SLA-2*02XX and SLA-3*04XX at a combined frequency of 30.1%, 18.4% and 34.5%, respectively, whereas DRB1*04XX, DQB1*02XX and DQA*02XX were the common class II alleles at 22.8%, 33.3% and 38.6%, respectively. The haplotype Lr-32.0 (SLA-1*07XX, SLA-2*02XX, SLA-3*04XX) and Lr-0.23 (DRB1*10XX-DQB1*06XX-DQA* 01XX) was the most common SLA class I and II haplotype, at 15.5% and 14.6%, respectively. Common class I and II combinations were also observed, which Lr-22.0/0.15 was the most predominant at 11.1%, followed by Lr-32.0/0.12 and Lr-4.0/0.2 at 10.8% and 7.9%, respectively. To our knowledge, this is the first report of SLA class I and II diversities in the commercial pigs in Southeast Asia. The information of the common SLA allele(s) in the population could facilitate swine genetic improvement and future vaccine design.